Measurement of needs of food security during flood disaster in Bera, Pahang, Malaysia / Nor Aini Hamidi - Hamidi, Nor Aini (2016)
Food security exists when all people, at all times, have physical and economic access to sufficient, safe and nutritious food to meet their dietary needs and food preferences for an active and healthy life. It comprises of food availability, food access, food utilization, and food stability. This paper studies the flood situation in Bera district area, by assessing the intensity of flood damages and its impacts on food security, which comes out with the measurement of needs of food security during flood. A cross sectional study was performed on 100 samples of population living in the affected area by using questionnaires adapted from Cambodia Post-Flood Relief and Recovery Survey 2012 and District and Community Questionnaire. These samples were selected randomly regardless of gender and age category. The results of this study were analyzed by using SPSS version 21.0. This study suggested that household composition and family income are linked to the household food security in terms of food consumption. There is a significant effect on the number of meals and quantity of the food consumed which shows less than usual, especially among the lowincome family and in family with more household composition. Therefore, further studies on measurement of needs of food security during disaster is required, to find out a better coping strategies of food insecurity faced by the disaster victims.